A practical representation of NFT pedagogy in a learning environment - Thusi, Nisi; Costa, King (My University, 2020)
Advanced pedagogy is the way to enhance teaching and learning performance for non-financial students. There are different methods in use across the globe for innovative teaching of higher learning students. The use of multimedia and technology empowers educational processes by increasing interaction between teachers and students. Hybrid teaching and blended learning follow an integrated approach to teaching that blends with students' interests and teacher's personality that needs curriculum-appropriate methods. Teachers should thus apply themselves to utilizing innovative methods so that the students’ learning process is as free-flowing and that the methodology used creates an atmosphere adaptable to conducive learning environment. The application of innovative teaching and learning methods is critical if we are to motivate and enculturate a spirit of learning and cooperation by encouraging others and doing your share on the part of students. The role of education is to ensure that while academic personal are involve in active teaching, an effort is made to ensure alignment between what is taught and what is comprehensible in relation to students. The goal of this study is an ongoing and progressive examine of how Edger Dale's Cone of Experience and Bloom's taxonomy is employed to positively influence student learning. In this conceptual research the methodology used was hinged on analytic processes for material already published in this area. Key variables under investigation forecast on integration of Dales and Blooms theories for theoretical perspectives with the researchers pedagogy known as the NFT.
Keywords: Collaborative Learning; Collective creativity; Innovative teaching and learning; Teacher education and methodology